Closed-Incision Negative Pressure Therapy and Abdominal Donor-Site Outcomes in DIEP Flap Breast Reconstruction: A Review of Current Evidence - Fayza Eka Zhafirah; Adelvia Nabunome; Agun Arya Wijaya; Herdina Mariyanti; Nadia Meilanda Intriani; Sekar Arum Firdausi (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: ciNPT is used to reduce abdominal donor-site complications in autologous breast reconstruction. Optimizing donor-site management is essential to prevent wound dehiscence, surgical site infection, seroma, hematoma, and delayed healing, which may prolong recovery and negatively affect postoperative outcomes. Methods: Systematic review of comparative studies (2020–2026) across six databases (PubMed, Scopus, Web of Science, SAGE Journals, ProQuest, ScienceDirect); methodological quality assessed using Joanna Briggs Institute (JBI) critical appraisal tools. Eight full-text studies evaluating ciNPT on abdominal donor-site incisions in adult patients undergoing autologous breast reconstruction were included. Results: ciNPT was consistently associated with reduced wound dehiscence and improved wound stability versus conventional care. Trends toward lower surgical site infection, seroma, hematoma, and complication-related re-intervention were observed, particularly in high-risk patients with elevated BMI or comorbidities. Some heterogeneity in study design and outcome definitions was noted. Conclusion: ciNPT is a promising adjunct for reducing abdominal donor-site complications in autologous breast reconstruction. Further high-quality randomized controlled trials with standardized outcomes and long-term follow-up are needed. Keywords: ciNPT, DIEP flap, donor site, breast reconstruction